2021
DOI: 10.1515/bmt-2020-0209
|View full text |Cite
|
Sign up to set email alerts
|

Surrogate based continuous noninvasive blood pressure measurement

Abstract: Arterial blood pressure is one of the most often measured vital parameters in clinical practice. State-of-the-art noninvasive ABP measurement technologies have noticeable limitations and are mainly based on uncomfortable techniques of complete or partial arterial occlusion by cuffs. Most commonplace devices provide only intermittent measurements, and continuous systems are bulky and difficult to apply correctly for nonprofessionals. Continuous cuffless ABP measurements are still an unmet clinical need and a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…While some studies argue that simple PAT measurements are inaccurate due to PEP variability [ 7 ] others have demonstrated better accuracy of PAT compared to PTT [ 8 ]. Extensive research on PAT has demonstrated its relative dependency on BP changes [ 4 , 5 , 9 , 10 ]. Still, a key challenge is the transformation of PAT as a single parameter to both SBP and DBP.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies argue that simple PAT measurements are inaccurate due to PEP variability [ 7 ] others have demonstrated better accuracy of PAT compared to PTT [ 8 ]. Extensive research on PAT has demonstrated its relative dependency on BP changes [ 4 , 5 , 9 , 10 ]. Still, a key challenge is the transformation of PAT as a single parameter to both SBP and DBP.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the heart is considered a periodic pressure pump based on Newton’s second law and the elasticity assumption. The Radial Resonance Theory (RRT) [ 23 ] was proposed in order that the arterial system is viewed as a transmission system for blood wave propagation and as a combination of various natural modes or inherent vibrations. RRT can provide a blood pressure calculation model and integrate the pulse wave signal with the body mass index to develop an extended linear model for blood pressure prediction.…”
Section: Methodologies and System Descriptionmentioning
confidence: 99%
“…It is expected that the faces in a dataset will be focused on, and computer training datasets can locate facial landmarks through facial alignment and angle. There are primarily 68 (x, y) coordinates for facial landmarks; these map facial points distributed across the chin (1-17), right eyebrow (18)(19)(20)(21)(22), left eyebrow (23)(24)(25)(26)(27), nose (28)(29)(30)(31)(32)(33)(34)(35)(36), right eye (37-42), left eye (43-48), and mouth (49-68). This paper introduces an additional 13 points on the forehead (69-81) to improve accuracy in the facial recognition, as shown in Figure 1.…”
Section: Facial Recognition and Normalizationmentioning
confidence: 99%
“…The most common noninvasive technique for BP measurement are based on uncomfortable arterial occlusion by inflatable cuffs where adequate accuracy is offered but only provide intermittent measurement and needs to be applied by professionals [3]. Recent advances in sensor technology have developed unobstructive cuffless devices to measure physiological parameters anytime.…”
Section: Introductionmentioning
confidence: 99%